Evaluation of Progress Selection of F2 - F6 Population, A Cross between Two Lowland Tomato Genotypes - Sautomo, Mohammad Wahyu; Syukur, Muhamad (Department of Agronomy and Horticulture, IPB University, 2017)
One of the parameters that can be measured from the activities of selection is progress selection. The population of a plant which has been selected is expected to be good against a derivative of a crop which was selected. The aim of this research is to study the results of progress selection varieties superior of tomato plants down the generations in the population F2 005001 until F6 005001-4-1-12-3 with a standard tomato cultivar, “Ratna”. The result showed that the selected genotypes have shown improvements over the standard cutivar in terms of weight per fruit, fruit weight per plant, the number of fruits per plant, fruit thickness and the age of harvested plants in the population F2-005001 until F6 005001-4-1-12-3. The mean against the character being observed in the population F2 005001 until F6 005001-4-1-12-3 indicated that the result is better if compared with both parents, P1 (SSH-5 ) and P2 (Intan) and the standard cultivar “Ratna”. The value of heritability a wider sense indicate its value being on each character of being selected, while the value of heritability in a more narrow sense showed a low value on every character. The value of progress against character selection of weights per fruit, the weight of the fruit per plant, the number of fruit per plant, thick ﬂesh fruit and the age of harvest showed increased slow progress in a genotype F2 005001 followed by a period of rapid progress in a genotype F4 005001-4-1 and very slow in a genotype F6 005001-4-1-12-3.